1995
DOI: 10.1161/01.cir.91.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Fibrosis and Stiffness With Hypertrophy and Heart Failure in the Spontaneously Hypertensive Rat

Abstract: The development of heart failure in the aging SHR is associated with marked myocardial fibrosis, increased passive stiffness, and impaired contractile function relative to age-matched nonfailing SHR and nonhypertensive control animals. These data suggest that fibrosis or events underlying the connective tissue response are important in the transition from compensated hypertrophy to failure in the SHR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
251
0
12

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 385 publications
(286 citation statements)
references
References 43 publications
23
251
0
12
Order By: Relevance
“…Our results are also consistent with investigations showing that cardioprotective treatments are mediated by a restoration or up-regulation of antioxidant enzymes (42,45). It is recognized that an increase in collagen concentration is an integral part of the extracellular matrix remodeling that takes place in the LVs during the natural aging process (66) and as well as in response to a variety of pathologies resulting in hypertrophy of this chamber (67,68). In accordance with these studies, we showed evidence of an increase of collagen deposition with aging and its exacerbation in aged SHR.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also consistent with investigations showing that cardioprotective treatments are mediated by a restoration or up-regulation of antioxidant enzymes (42,45). It is recognized that an increase in collagen concentration is an integral part of the extracellular matrix remodeling that takes place in the LVs during the natural aging process (66) and as well as in response to a variety of pathologies resulting in hypertrophy of this chamber (67,68). In accordance with these studies, we showed evidence of an increase of collagen deposition with aging and its exacerbation in aged SHR.…”
Section: Discussionsupporting
confidence: 92%
“…However, in the non-compensatory phase, fibrosis and stiffness of the myocardial interstitium were suppressed by BPS administration and diastolic function was maintained [3,24]. The changing point from the compensatory phase to the non-compensatory phase was determined by arterial stiffness induced by pressure overload or cardiac hypertrophy through coronary circulation failure [4,10]. BPS effectively suppresses myocardial degeneration and fibrosis in chronic heart failure by improvement of coronary circulation and an anticytokine effect.…”
Section: Discussionmentioning
confidence: 99%
“…The first studies for the clinical detection of heart failure signs in rats were carried out by Bing and cols. that studied spontaneously hypertensive rats with heart dysfunction [68][69][70] . The data on the incidence of post-infarction heart failure and the possibility of its clinical recognition in rats, however, are scarce.…”
Section: Morphological Functional and Clinical Evaluation Of Heart Fmentioning
confidence: 99%